Effects of continuous positive airway pressure and isocapnic‐hypoxia on cerebral autoregulation in patients with obstructive sleep apnoea. (1st December 2016) - Waltz, Xavier; Beaudin, Andrew E.; Hanly, Patrick J.; Mitsis, Georgios D.; Poulin, Marc J.
Abstract : Key points: Altered cerebral autoregulation (CA) in obstructive sleep apnoea (OSA) patients may contribute to increased stroke risk in this population; the gold standard treatment for OSA is continuous positive airway pressure, which improves cerebrovascular regulation and may decrease the risk of stroke. Isocapnic‐hypoxia impairs CA in healthy subjects, but it remains unknown in OSA whether impaired CA is further exacerbated by isocapnic‐hypoxia and whether it is improved by treatment with continuous positive airway pressure. During normoxia, CA was altered in the more severe but not in the less severe OSA patients, while, in contrast, during isocapnic‐hypoxia, CA was similar between groups and tended to improve in patients with more severe OSA compared to normoxia. From a clinical perspective, one month of continuous positive airway pressure treatment does not improve CA. From a physiological perspective, this study suggests that sympathetic overactivity may be responsible for altered CA in the more severe OSA patients. Abstract: Cerebral autoregulation (CA) impairment may contribute to the increased risk of stroke associated with obstructive sleep apnoea (OSA). It is unknown if impaired CA is further exacerbated by isocapnic‐hypoxia and whether it is improved by treatment of OSA with continuous positive airway pressure (CPAP). CA was assessed during wakefulness in 53 OSA patients (50.3 ± 9.3 years) and 21 controls (49.8 ± 8.6 years) at baseline and following a minimum of 1 month of effective CPAP therapy (OSA patients, n = 40). Control participants ( n = 21) performed a follow‐up visit to control for time effects within OSA patients between baseline and the post‐CPAP visit. Beat‐by‐beat middle cerebral artery blood flow velocity and mean arterial blood pressure (MBP), and breath‐by‐breath end‐tidal partial pressure of CO2 ( P ET, C O 2 ) were monitored. CA was determined during normoxia and isocapnic‐hypoxia using transfer function (phase and gain) and coherence analysis (including multiple and partial coherence (using MBP and P ET, C O 2 as inputs)) in the very low frequency range (0.03–0.07 Hz). OSA patients were divided into two subgroups (less severe and more severe) based upon the median respiratory disturbance index (RDI). During normoxia, the more severe OSA patients (RDI 45.9 ± 10.3) exhibited altered CA compared to controls and the less severe OSA patients (RDI 24.5 ± 5.9). In contrast, during isocapnic‐hypoxia, CA was similar between groups. CPAP had no effect on CA. In conclusion, CA is altered in the more severe OSA patients during normoxia but not during isocapnic‐hypoxia and CPAP treatment does not impact CA. Key points: Altered cerebral autoregulation (CA) in obstructive sleep apnoea (OSA) patients may contribute to increased stroke risk in this population; the gold standard treatment for OSA is continuous positive airway pressure, which improves cerebrovascular regulation and may decrease the risk of stroke. Isocapnic‐hypoxia impairs CA in healthy subjects, but it remains unknown in OSA whether impaired CA is further exacerbated by isocapnic‐hypoxia and whether it is improved by treatment with continuous positive airway pressure. During normoxia, CA was altered in the more severe but not in the less severe OSA patients, while, in contrast, during isocapnic‐hypoxia, CA was similar between groups and tended to improve in patients with more severe OSA compared to normoxia. From a clinical perspective, one month of continuous positive airway pressure treatment does not improve CA. From a physiological perspective, this study suggests that sympathetic overactivity may be responsible for altered CA in the more severe OSA patients.